Synthesis of Diimidazole Has Pyrazole, Isoxazole and Pyrimidine Derivatives and Evaluation as Antibacterial - Sahar Abdullah Kadham.1, Abdul Jabar Kh. Atia2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
New diimidazole contains pyrazole , isoxazole and thiopyrimidine were synthesized by using simple methods . All compounds were synthesized by using hippuric acid (1) as stating material which was obtained from benzoyl and glycine with. pyrazole derivatives (6a – b ) was obtained from reaction (5a – b) with hydrazine hydrate while reaction of (5a – b )with hydroxyl amine isoxazole derivatives (7a – b) were obtained ,finally reaction of thiourea was reacted with 5a – b thiopyrimidine derivatives were get (8a –b ) . FTIR and 1HNMR spectra were used to characterized derivatives several bacterial species like Pseudomonas aeruginosa , Staphylococcus aureus, and Acinetobacter baumanii were used to tested antibacterial activity